PENGARUH TINGKAT MOTIVASI SISWA TERHADAP JAM TIDUR DAN NILAI UJIAN MENGGUNAKAN METODE MANOVA - Amelia Kurnia Fitri; Hanni Putria Hartanti; Sri Pingit Wulandari (Integrative Perspectives of Social and Science Journal, 2024)
Background: High motivation encourages students to study harder but often reduces their sleep duration, which can negatively impact their concentration and exam performance. Conversely, students with low motivation may have more regular sleep patterns but are less focused on academic activities, which affects their performance. Purpose: This study aims to examine the influence of students' motivation levels on their sleep duration and exam scores using MANOVA analysis. MANOVA (Multivariate Analysis of Variance) is a statistical technique used to simultaneously test the significance of mean differences among groups for two or more dependent variables. Methods: The study involves several analytical steps, including testing the multivariate normal distribution assumption, Bartlett’s test (independence) to assess the homogeneity of variance-covariance, simultaneous testing to identify differences among categories of student motivation levels, multiple comparison testing using LSD (Least Significant Difference) to determine specific categories with differences, and evaluating the grouping results to identify the most significant influence of motivation levels on sleep duration and exam scores. Results: The analysis revealed that most students have moderate motivation levels. In the MANOVA assumption test, the data showed a normal distribution among dependent variables, but the assumption of homogeneity of variance was not met. The analysis indicated that high motivation levels had the most significant influence, whereas moderate and low motivation levels did not have a significant impact on students’ sleep duration and exam scores. Conclusion: Multiple comparison testing with LSD revealed that the average sleep duration was similar across low, moderate, and high motivation levels. However, there were differences in the average exam scores among students with low, moderate, and high motivation levels.